MiR-143-3p Inhibits Osteogenic Differentiation of Human Periodontal Ligament Cells by Targeting KLF5 and Inactivating the Wnt/β-Catenin Pathway - Wangzhou, Kaixin; Lai, Zhiying; Lu, Zishao; Fu, Wanren; Liu, Cheng; Liang, Zhengeng; Tan, Yi; Li, Conghui; Hao, Chunbo (Frontiers in Physiology, 2021)
Human periodontal ligament cells (hPDLCs) play a vital role in cell regeneration and tissue repair with multi-directional differentiation potential. microRNAs (miRs) are implicated in the osteogenesis of hPDLCs. This study explored the mechanism of miR-143-3p in osteogenesis of hPDLCs. Osteogenic differentiation of isolated hPDLCs was induced. KLF5 expression during osteogenic differentiation of hPDLCs was detected and then silenced in hPDLCs. Binding relationship between KLF5 and miR-143-3p was predicted and verified. hPDLCs were treated with miR-143-3p mimic or overexpressing KLF5, and then osteogenic specific markers and mineralized nodules were measured. The key factors of the Wnt/β-catenin pathway during osteogenesis of hPDLCs were measured. KLF5 expression was upregulated during osteogenesis of hPDLCs. KLF5 silencing or miR-143-3p mimic reduced osteogenic specific markers and mineralized nodules. Overexpression of KLF5 could reverse the inhibitory effect of miR-143-3p on osteogenic differentiation. miR-143-3p mimic and KLF5 silencing inactivated the Wnt/β-catenin pathway. Activation of the Wnt/β-catenin pathway reversed the repression effect of miR-143-3p mimic on osteogenesis of hPDLCs. In conclusion, miR-143-3p inhibited osteogenic differentiation of hPDLCs by targeting KLF5 and inactivating the Wnt/β-catenin pathway.